The energization of KwaBhaza : a case study in rural energy and development - Kloot, Bruce (Energy Research Centre, 2023)
Energization can be described as a form of integrated energy delivery. In the case of the KwaBhaza Pilot Project, PV and LPGas were combined. in a package and offered to rural households. While the approach to off-grid electrification and distributed energy services tends to emphasise the technical aspects of delivery (Kotze 1998), this work provides some insight into the anthropological aspects that hinder the implementation of such initiatives. In this context, 'anthropological aspects' do not refer to cultural conditions in the field but rather the anthropology of development, expressed as a holistic examination of the project and a critical assessment of the development framework within which it operates. It is with this in mind that the objectives of energization, as a development initiative, are thoroughly explored.